2019
DOI: 10.3389/fncel.2019.00380
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effects of HMGB-1 Require Microglial-Astroglial Interaction: Implications for the Status Epilepticus -Induced Neuroinflammation

Abstract: Temporal Lobe Epilepsy (TLE) is the most common form of human epilepsy and available treatments with antiepileptic drugs are not disease-modifying therapies. The neuroinflammation, neuronal death and exacerbated plasticity that occur during the silent period, following the initial precipitating event (IPE), seem to be crucial for epileptogenesis. Damage Associated Molecular Patterns (DAMP) such as HMGB-1, are released early during this period concomitantly with a phenomenon of reactive gliosis and neurodegener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 72 publications
5
56
1
Order By: Relevance
“…Moreover, overexpression of a plethora of proinflammatory cytokines was observed in the brain of SARS-CoV-infected mice, most notably IL-6, interferon (IFN)-γ, chemokine (C-C motif) ligand (CCL)-2, and CCL12 ( Glass et al., 2004 ; McCray et al., 2007 ; Tseng et al., 2007 ) and also in cases reported in humans ( Xu et al., 2005 ). We now know that astrocytes are highly sensitive to increased proinflammatory mediators and that this stimulus induce a proinflammatory gene expression program in astrocytes ( Liddelow and Barres, 2017 ; Rosciszewski et al., 2019 ; Verkhratsky et al., 2019 ).…”
Section: Severe Acute Respiratory Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, overexpression of a plethora of proinflammatory cytokines was observed in the brain of SARS-CoV-infected mice, most notably IL-6, interferon (IFN)-γ, chemokine (C-C motif) ligand (CCL)-2, and CCL12 ( Glass et al., 2004 ; McCray et al., 2007 ; Tseng et al., 2007 ) and also in cases reported in humans ( Xu et al., 2005 ). We now know that astrocytes are highly sensitive to increased proinflammatory mediators and that this stimulus induce a proinflammatory gene expression program in astrocytes ( Liddelow and Barres, 2017 ; Rosciszewski et al., 2019 ; Verkhratsky et al., 2019 ).…”
Section: Severe Acute Respiratory Syndromementioning
confidence: 99%
“…Reactive gliosis is a fine graded and highly conserved mechanism of astroglial response to injury, and, in general terms, it is supposed to be aimed to improve neuronal survival, to restore BBB, and to isolate the injured area by providing glial scar formation ( Sofroniew and Vinters, 2010 ; Anderson et al., 2016 ; Verkhratsky et al., 2019 ). However, under certain not yet completely defined circumstances, but probably involving proinflammatory microglial activation and toll-like/NF-κB/STAT3-dependent pathways, astrocytes may engage into a proinflammatory gene expression program also called maladaptive reactive astrogliosis that transforms astrocytes into proinflammatory and proneurodegenerative cells ( Pekny et al., 2016 ; Liddelow et al., 2017 ; Rosciszewski et al., 2018 , 2019 ; Zorec et al., 2019 ). Transcriptomic analyses of reactive astrocytes have also identified this spectrum of possible activation profiles ranging between two extreme phenotypes that were simplistically defined as the proinflammatory proneurodegenerative A1 phenotype and the proneuronal survival immunomodulatory A2 phenotype, but these studies also showed mixed reactive profiles characterized by the expression of PAN-reactive genes ( Hamby et al., 2012 ; Zamanian et al., 2012 ; Anderson et al., 2016 ; Burda and Sofroniew, 2017 ; Liddelow and Barres, 2017 ; Liddelow et al., 2017 ; Clarke et al., 2018 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, microglial cells show age-dependent and regionspecific changes in morphology such as structural deterioration or dystrophy, decreased expression of growth/neurotrophic factors, and an impaired phagocytic activity in the face of increased marker expression and upregulation of pro-inflammatory molecules (see Niraula et al, 2017, and references herein), all of which are associated to a gradual loss of As and microglia neuroprotective capacity. Reportedly, microglia switch to a so-called ''primed'' status, endowed with a strong neurotoxic, pro-inflammatory M1 phenotype with harmful consequences for As-neuron interactions (Miller and Streit, 2007;Liddelow et al, 2017;Rosciszewski et al, 2018Rosciszewski et al, , 2019 and DAergic neuron survival upon injury (L'Episcopo et al, 2011a(L'Episcopo et al, ,b,c, 2018a.…”
Section: Introductionmentioning
confidence: 99%
“…In light of current findings, it is proposed that stress-induced increases in glucocorticoids activates glucocorticoid receptors and subsequently increases HMGB1 release from CNS astrocyte. Extracellular HMGB1 interact with TLR2, TLR4, and RAGE which express in astrocyte and microglia [67,68] to induce innate immunity activation [69]. Astrocyte-derived HMGB1 could then be involved in neuroinflammatory processes which, in turn, mediate psychiatric disorders such as MDD.…”
Section: Discussionmentioning
confidence: 99%